Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
0,5 . x - \(\frac{3}{7}\) : \(\frac{1}{2}\)= 1 \(\frac{1}{7}\)
\(\frac{1}{2}\). x - \(\frac{3}{7}\)x \(\frac{2}{1}\)= \(\frac{8}{7}\)
\(\frac{1}{2}\) . x - \(\frac{6}{7}\) = \(\frac{8}{7}\)
\(\frac{1}{2}\) . x = \(\frac{8}{7}\) + \(\frac{6}{7}\)
\(\frac{1}{2}\) . x = \(\frac{14}{7}\)
\(\frac{1}{2}\) . x = 2
x = 2 : \(\frac{1}{2}\)
x = 4
Vậy x = 4
\(b^2=ac\)
\(\Rightarrow\frac{a}{b}=\frac{b}{c}\)
Đặt \(\frac{a}{b}=\frac{b}{c}=k\), ta có: \(a=bk;b=ck\)
\(\frac{a}{c}=\frac{bk}{c}=\frac{ck\times k}{c}=k^2\) (1)
\(\left(\frac{a+2012b}{b+2012c}\right)^2=\left(\frac{bk+2012b}{ck+2012}\right)^2=\left(\frac{b\left(k+2012\right)}{c\left(k+2012\right)}\right)^2=\left(\frac{b}{c}\right)^2=k^2\) (2)
Từ (1) và (2)
=> \(\frac{a}{c}=\left(\frac{a+2012b}{b+2012c}\right)^2\left(\text{đ}pcm\right)\)
\(\frac{L}{340}-\frac{L}{6100}=0.5\Leftrightarrow L\left(\frac{1}{340}-\frac{1}{6100}\right)=0.5\)\(\Leftrightarrow L=\frac{0.5}{\frac{1}{340}-\frac{1}{6100}}\)
em tự giải ra kết quả nhé.
\(\frac{L}{340}\) - \(\frac{L}{6100}\) = 0,5. Tìm L